2023
DOI: 10.3389/fgene.2023.1088455
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutation and deletion contribute to tumor immune evasion

Abstract: TP53 (or p53) is widely accepted to be a tumor suppressor. Upon various cellular stresses, p53 mediates cell cycle arrest and apoptosis to maintain genomic stability. p53 is also discovered to suppress tumor growth through regulating metabolism and ferroptosis. However, p53 is always lost or mutated in human and the loss or mutation of p53 is related to a high risk of tumors. Although the link between p53 and cancer has been well established, how the different p53 status of tumor cells help themselves evade im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 120 publications
0
3
1
Order By: Relevance
“…Upregulated p53 mediates cell cycle arrest and apoptosis, eliminating damaged cells [15] when oncogenic signals are present. In contrast, mutated p53 may increase PD-L1 expression by activating various cytokines, leading to the conversion of in ltrating T into depleted CD8 + T cells, counteracting the effects of PD-1 inhibitors [14]. However, our patient showed high P53 expression in immunohistochemistry, while intriguingly, NGS analysis did not reveal any mutation in the P53 gene.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Upregulated p53 mediates cell cycle arrest and apoptosis, eliminating damaged cells [15] when oncogenic signals are present. In contrast, mutated p53 may increase PD-L1 expression by activating various cytokines, leading to the conversion of in ltrating T into depleted CD8 + T cells, counteracting the effects of PD-1 inhibitors [14]. However, our patient showed high P53 expression in immunohistochemistry, while intriguingly, NGS analysis did not reveal any mutation in the P53 gene.…”
Section: Discussioncontrasting
confidence: 53%
“…As for tumor immune escape, Berger [13] concluded that PD-1, an immune checkpoint belonging to the immunoglobulin B7-CD28 family, plays a negative regulatory role in the human immune response by inhibiting T cell activation, proliferation, and inducing T cell death [13]. Suppression of PD-1 results in a signi cant reduction in T cells numbers, leading to immune evasion by tumor cells [14]. Therefore, PD-1 blockade can attenuate the inhibitory effect on T cell activation, fostering the activation of the endogenous anti-tumor immune response and providing a novel therapeutic pathway for tumor patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our results, both FAs and PTs harbor a variety of mutations, including missense, nonsense, frame-shift, insertion, and deletion, while the most frequent ones are missense mutations. These mutations likely involve a crucial region, such as a catalytic site or an interaction domain, to cause the loss of its original functions, including regulation of transcription [ 19 , 20 ], aberrant activation, or loss of signaling pathways [ 21 ]. We constructed the interaction network between the specific mutation and expression profiles to find the core mutated genes and their probable regulation on target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown a significant increase in the percentage of positive TUNEL staining in breast cancer cells treated with Huaier (Wang et al, 2012;Qi et al, 2016). Activation of p53 leads to apoptosis (Liu et al, 2023). Zhang et al showed that p53 accumulated and was activated in MCF-7 cells in response to Huaier treatment (Zhang et al, 2010).…”
Section: Huaier Promotes Apoptosis In Breast Cancer Cellsmentioning
confidence: 96%